The impact of psychological capital on prosocial behaviour: a systemic review - Tongbin, Luo; Ma’rof, Aini Azeqa (Human Resources Management Academic Research Society, 2024)
To systematically evaluate the impact of psychological capital on individual prosocial behaviour. Methodology: Literature searches were conducted in the Scopus, APA PsycInfo, and PubMed databases for studies on the relationship between psychological capital and prosocial behaviour. Selected articles underwent quality assessment, and relevant data were extracted for a comprehensive review of the influence of psychological capital on prosocial behaviour. Results: A total of 6 studies were included, involving 41 independent effect sizes and 3203 participants. Findings that women exhibit higher levels of empathy and perspective taking than men, and they have higher levels of prosocial. Psychological capital positively predicts prosocial behaviour, and yoga and meditation can enhance psychological capital. Conclusion: Psychological capital can positively predict prosocial behaviour. Yoga and meditation can promote individuals' positive psychological capital.